2009
DOI: 10.1038/embor.2009.31
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐directed DNA methylation requires an AGO4‐interacting member of the SPT5 elongation factor family

Abstract: Recent studies have identified a conserved WG/GW-containing motif, known as the Argonaute (AGO) hook, which is involved in the recruitment of AGOs to distinct components of the eukaryotic RNA silencing pathways. By using this motif as a model to detect new components in plant RNA silencing pathways, we identified SPT5-like, a plant-specific AGO4-interacting member of the nuclear SPT5 (Suppressor of Ty insertion 5) RNA polymerase (RNAP) elongation factor family that is characterized by the presence of a carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 29 publications
(46 reference statements)
5
145
0
3
Order By: Relevance
“…Mutational studies of these sites revealed that arginine methylation affects SPT5s association with RNA polymerase II and enhances the ability of SPT5 to mediate DRB-inhibited transcription (61). Thus, reduced arginine methylation of SPT5 affects its promoter association and transcriptional elongation.…”
Section: Identification Of Endogenous Arginine Mono-methylation (Mma)mentioning
confidence: 99%
“…Mutational studies of these sites revealed that arginine methylation affects SPT5s association with RNA polymerase II and enhances the ability of SPT5 to mediate DRB-inhibited transcription (61). Thus, reduced arginine methylation of SPT5 affects its promoter association and transcriptional elongation.…”
Section: Identification Of Endogenous Arginine Mono-methylation (Mma)mentioning
confidence: 99%
“…The AGO4/siRNA complexes are recruited to target loci via base-pairing with scaffold transcripts generated by RNA polymerase Pol V (Pontier et al, 2005;Mosher et al, 2008;Wierzbicki et al, 2008Wierzbicki et al, , 2009). The recruitment of AGO4 to chromatin may also be facilitated by its interaction with the GW/WGrich extensions of NRPE1 (the largest subunit of Pol V) Pontes et al, 2006;El-Shami et al, 2007;Li et al, 2008) and KTF1/SPT5L (a transcription elongation factor) (Bies-Etheve et al, 2009;He et al, 2009). The conserved GW/WG motif, defining an "Ago hook," is widely present in factors implicated in AGO actions (Azevedo et al, 2011;Garcia et al, 2012;Pontier et al, 2012).…”
Section: Dna Methylationmentioning
confidence: 99%
“…DsRNAs are synthesized by RDR2 using Pol IV transcripts as a template, processed into 24-nt siRNAs by DCL3, and loaded into AGO4 (Matzke et al 2009). AGO4 interacts with the Pol V subunit NUCLEAR RNA POLYMERASE E1 (NRPE1) possibly through a base-pairing interaction between AGO4-loaded siRNA and nascent Pol V transcripts (El-Shami et al 2007), which is aided by the SUPPRESSOR OF TY INSERTION 5-LIKE (SPT5L, also known as KOW domain-containing transcription factor 1; KTF1) (Bies-Etheve et al 2009). These RNAmediated protein interactions may be recognized by INVOLVED IN DE NOVO 2 (IDN2), which may recruit methylation machinery including DRMs to establish de novo methylation (Ausin et al 2009).…”
Section: Factors Involved In Rddm and Maintenance Of Dna Methylationmentioning
confidence: 99%